2022
DOI: 10.1038/s41467-022-29062-5
|View full text |Cite|
|
Sign up to set email alerts
|

Structures of a deltacoronavirus spike protein bound to porcine and human receptors

Abstract: Porcine deltacoronavirus (PDCoV) can experimentally infect a variety of animals. Human infection by PDCoV has also been reported. Consistently, PDCoV can use aminopeptidase N (APN) from different host species as receptors to enter cells. To understand this broad receptor usage and interspecies transmission of PDCoV, we determined the crystal structures of the receptor binding domain (RBD) of PDCoV spike protein bound to human APN (hAPN) and porcine APN (pAPN), respectively. The structures of the two complexes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 64 publications
1
25
0
Order By: Relevance
“…Our previous study and Liu et al. also reported that PDCoV S protein had a higher binding affinity with human APN receptor than pig (Ji et al., 2022; Liu et al., 2021). A previous study by G. Li et al.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Our previous study and Liu et al. also reported that PDCoV S protein had a higher binding affinity with human APN receptor than pig (Ji et al., 2022; Liu et al., 2021). A previous study by G. Li et al.…”
Section: Discussionmentioning
confidence: 79%
“…Unexpectedly, the PDCoV shared the highest adaptation to G. gallus, moderate to H. sapiens, and the lowest to S. scrofa (Figure 7). Thus, we speculated that although PDCoV was isolated from S. scrofa, H. sapiens and G. gallus may also be highly susceptible to PDCoV infection, indicating the high risk of direct transmission that PDCoV S protein had a higher binding affinity with human APN receptor than pig (Ji et al, 2022;Liu et al, 2021). A previous study by G. Through comprehensively analyzing the CUB of PDCoV, we found that a certain CUB exists in the genome, in which nucleotides U and G are ended over-represented and low-represented codons, respectively.…”
Section: Similarity Index Analysis Between Pdcov and Hostsmentioning
confidence: 99%
“…PDCoV was identifed from a surveillance study in swine and currently is increasing in prevalence in Southeast Asia and has been detected globally, which caused signifcant losses to the swine industry. Moreover, human cases with PDCoV infection were reported and PDCoV can use human APN for entry into host cells, indicating the great threat of PDCoV to public health [11,16]. As a newly emerged swine virus, there are no licensed vaccines and antiviral drugs available for the swine industry.…”
Section: Discussionmentioning
confidence: 99%
“…Te PDCoV strains CZ2020-F80 and CZ2020-F100 are the passage of the 80 th and 100 th strains of CZ2020, respectively. Pig anti-PDCoV polyclonal antibody was produced in our laboratory and was well characterized [16]. Goat anti-pig IgG H&L (FITC) (ab6911) was purchased from Abcam.…”
Section: Introductionmentioning
confidence: 99%
“…PDCoV has the smallest genomic RNA in coronaviruses ( 5 ), which means increased prevalence and pathogenicity. Investigation of the crystal structure of PDCoV and its receptors provided further insights into the transmission of PDCoV among species ( 6 ). Recently, infections of PDCoV among Haitian children were identified by researchers ( 7 ), suggesting the potential of PDCoV to transmit from animals to humans.…”
Section: Introductionmentioning
confidence: 99%